2018
DOI: 10.1186/s41747-018-0070-5
|View full text |Cite
|
Sign up to set email alerts
|

Using body mass index to estimate individualised patient radiation dose in abdominal computed tomography

Abstract: BackgroundThe size-specific dose estimate (SSDE) is a dose-related metrics that incorporates patient size into its calculation. It is usually derived from the volume computed tomography dose index (CTDIvol) by applying a conversion factor determined from manually measured anteroposterior and lateral skin-to-skin patient diameters at the midslice level on computed tomography (CT) localiser images, an awkward, time-consuming, and not highly reproducible technique. The objective of this study was to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 14 publications
0
32
0
1
Order By: Relevance
“…For tumour, the DLP values ranged from 870 mGy.cm [ 15 ] to 950 mGy.cm [ 35 ]. For oncologic follow-up, the DLP values ranged from 605 mGy.cm [ 36 ] to 970 mGy.cm [ 34 ]. One publication presents DRL ci for abdominal CT, both for males and females [ 16 ], demonstrating however similar values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For tumour, the DLP values ranged from 870 mGy.cm [ 15 ] to 950 mGy.cm [ 35 ]. For oncologic follow-up, the DLP values ranged from 605 mGy.cm [ 36 ] to 970 mGy.cm [ 34 ]. One publication presents DRL ci for abdominal CT, both for males and females [ 16 ], demonstrating however similar values.…”
Section: Resultsmentioning
confidence: 99%
“…The huge variations in the reported CT dose descriptors values for almost all the clinical indications addressed above are likely to be explained by differences in protocols (exposure parameters and scan length), type and age of scanner, number of acquisition series and, in the specific case of CCTA, by the option of performing either prospective or retrospective acquisitions. The same variations in radiation doses for CT across patients is described in the literature, and the reasons are primarily related on how CT scanners are used [ 34 ], the differences in patient’s size (weight and height) [ 36 ] and to the level of image quality required to answer the clinical question [ 35 ]. Although the DRLs are defined for standard patients [ 4 ], taking into consideration that the weight and height of patients are also a determining factor for dose increase, categorising patients by body mass index should be considered in the near future [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…BMI data can also be used to approximate size specific dose estimates which take patient size into consideration when describing patient dose. 22 Quantitative measures of size would provide better data for the determination of the causes of red alerts. Also, due to difficulty with data transmission from the CT scanners to DoseWatch in Period 1, dose data of many brain and abdominopelvic CT examinations could not be retrieved for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Informed consent to proceed with both SDCT and ULDCT was obtained prior to proceeding with imaging. Body mass index (BMI) was not prospectively collected and not retrospectively available, so BMI was estimated using the method described by O'Neill et al [9], who reported good correlation between BMI and imaging measurements (r = 0.88).…”
Section: Designmentioning
confidence: 99%